Damage localization on CFRP composites by electrical impedance tomography. (August 2022) - Rocha, Helena; Fernandes, Christophe; Ferreira, Nelson; Lafont, Ugo; Nunes, João P.
Abstract: This work exploited the use of electrical impedance tomography (EIT) with one-step difference Gaussian-Newton (GN) algorithm to detect different types of damage on unidirectional carbon fibre/epoxy composite laminates. The major challenge concerning the implementation of EIT on composite materials has to do with their anisotropy. To assess this issue, this study was conducted on carbon fibre composites having different layup configurations with different degrees of anisotropy: a quasi-isotropic layup, to approximate as much as possible these layered materials to an isotropic material, and an unbalanced layup, with further degree of anisotropy. Damage detection in the highly anisotropic unbalanced laminates is a major challenge for EIT technique, which has not been assessed before in the literature. Severe damage, in the form of through-thickness holes, was created in the laminates with different diameters and at two locations of the specimen to evaluate the sensitivity of this technique to damage size and its capacity to detect multiple damages. EIT showed progressive decrease of electrical conductivity as the diameter of through-thickness holes increased. Impact damages of different severities were also created. The EIT technique was able to distinguish different damage shapes in the laminates with different anisotropy. EIT identified elongated shaped damages, produced by impact events of different impact energies, on unbalanced laminates. However, the EIT images overestimate the damaged area, as compared to non-destructive ultrasonic inspections. The EIT images of the quasi-isotropic laminates revealed damage in the central area of the specimens, but a well-defined damage shape could not be distinguished. Graphical Abstract: ga1